THE IMPACT OF VAT POLICY, SALES TAX ON LUXURY GOODS, AND IMPORT DUTY TOWARDS THE SUPPRESSION OF COMPLETELY BUILT-UP - Maitimu, Christi Stevany; Manurung, Jean P.; Tobing, Fenny BNL. (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
This study is conducted based on the progress and development of industrial industry especially automotive industry. Motor vehicles that function to facilitate transportation and mobility of the society can also be an indicator for the level of economic growth in a region. The ownership of a motor vehicle especially cars now become a prestige for the owners, especially Completely Built-Up (CBU) or imported cars with large cc or above 3000cc. Tax revenues in automotive sector also contribute in central and regional governments revenues, such as, Value-Added Tax (VAT), Sales Tax on Luxury Goods, and import duty. The data of this study are collected through observation method at GAIKINDO (motor vehicle association as a reference of the data of this study) in 2012-2016, interview, and documentary study. Moreover, the data analysis procedure of this study is quantitative analysis by doing: (1) classical assumption test which is normality test, multicollinearity test, and heteroscedasticity test, (2) hypothesis test which is multiple linear regression test, coefficient of determination test (R2), statistical test t, and statistical test f. Data analysis technique used in this study is multiple linear regression analysis which serves to prove the research hypothesis. The data that has met the classical assumption is processed so as to produce the regression equation as follows Y = 0.751 X ¹ + 0.872 X². it is known from the result of the quantitative analysis that they are valid and reliable because the results of statistical calculations show the value of F arithmetic = 47.503 with a significance of 0.000 <0.05. F count 47.503> f table 3.16 with a significance level of 0.000. Using the 0.05 significance limit, coefficient of determination from table model summary it can be seen that the adjusted R square (R²) is 0.900. Thus, the contribution of influence from independent variable is 62,5% while the rest equal to 37,5% influenced by other factors which are not examined. From assumptions test received, it is proven that there is impact of imposition of VAT, Sales Tax on Luxury Goods, and import duties on car sales to suppress the intact import of CBU cars that increase investor interest for direct investment CBU cars in Indonesia.Keywords: government policy, VAT, Sales Tax on Luxury Goods, import duty, Completely Built-Up (CBU)